The Oxford handbook of early Christian biblical interpretation - Blowers, Paul M. (Oxford handbooks online Religion, 2019)
The Bible was the lifeblood of virtually every aspect of the life of the early churches. This handbook explores a wide array of themes related to the reception, canonization, interpretation, uses, and legacies of the Bible in early Christianity